2020
DOI: 10.1002/jcp.29998
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod on morphology and function in testis and epididymis of Cricetulus barabensis

Abstract: Photoperiod regulates the seasonal reproductive rhythms of mammals by influencing the development and function of sexual organs; however, the underlying mechanism remains unclear. We examined the morphology and functioning of the main sex organs of striped dwarf hamsters (Cricetulus barabensis) under different photoperiods (short daylight [SD], moderate daylight [MD], and long daylight [LD]) and further investigated the underlying molecular mechanisms. There was an inverse correlation between blood melatonin l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 69 publications
(99 reference statements)
4
6
0
Order By: Relevance
“…Furthermore, TUNEL staining showed obviously DNA fragmentation in the testicular, suggesting the occurrence of apoptosis in the SM and SL groups. Previous studies on Syrian hamsters and striped dwarf hamsters have shown that short daylight exposure can induce apoptosis in testicular cells (Mou et al, 2021;Seco-Rovira et al, 2015), this consistent with our results. It is worth noting that although an increase in apoptosis may lead to a decrease in the number of mitochondria, our results showed that the number of mitochondria in the two groups decreased but ATP synthase activity remained stable.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, TUNEL staining showed obviously DNA fragmentation in the testicular, suggesting the occurrence of apoptosis in the SM and SL groups. Previous studies on Syrian hamsters and striped dwarf hamsters have shown that short daylight exposure can induce apoptosis in testicular cells (Mou et al, 2021;Seco-Rovira et al, 2015), this consistent with our results. It is worth noting that although an increase in apoptosis may lead to a decrease in the number of mitochondria, our results showed that the number of mitochondria in the two groups decreased but ATP synthase activity remained stable.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, short daylight is reported to affect the testis of the spiny mouse (Acomys cahirinus), Anderson's gerbil (Gerbillus andersoni), and Syrian hamster (El-Bakry et al, 1998;Martinez-Hernandez et al, 2020), including a decrease in testicular germ cells, atrophy of spermatogonia, and a decrease in testicular weight and volume. Our previous results also showed that the testicular structure in striped dwarf hamsters is significantly degraded under short daylight compared with long and moderate daylight conditions (Mou et al, 2021). However, the molecular mechanisms underlying how short daylight and low temperature exposure trigger these changes remain unclear.…”
Section: Introductionmentioning
confidence: 90%
“…The notable findings on the efferent duct and ductus deferens histo-morphometric data from this study, concurs with the report of Calvo et al (1997) in Syrian Hamster, Cruceno et al (2013) in wild rodent Viscacha ( Lagostomus maximus maximus ) Grahmajo-Bühler et al (2015) in Chinchilla lanigera Grey and Mou et al (2020) in striped dwarf hamster. However, markedly lower luminal and ductal diameters were reported for proximal efferent duct by Aire et al (1979) and Abdul-Rahman and Jeffcoate (2018) in the same guinea fowl cock.…”
Section: Discussionsupporting
confidence: 93%
“…Artificial lighting regimes and exogenous melatonin administration may be used to influence the reproductive functions of birds with respect to annual changes. Recently, biostimulation using photoperiod ( Ogawa et al,1993 ; Calvo et al, 1997 ; Cruceño et al, 2013 ; Mou et al, 2020 ; Baso et al, 2022 ) and melatonin ( Juss et al, 1993 ; Shiu et al, 2000 ; Mousa-Balabel and Mohamed, 2011 ; Assia and Boulakoud, 2014 ) to improve reproductive efficiency in male reproductive organs of mammals and birds have become common practice.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of tubular diameters and epithelial thickness of epididymal duct were performed using ImageJ. Measurements of epithelial thickness and lumen diameter were performed according to previous reports [50,51]. Briefly, 10 samples were used to analyze epididymal tubule diameter and epithelial thickness in each group (Bilateral epididymides of 5 mice).…”
Section: Histological Examinationmentioning
confidence: 99%